Business model design and learning : a strategic guide - Spencer, Barbara ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2013)
The purpose of this book is to explain what a business model is, what you have to do to get one, and what to do about the one you've already got. It contends that to be successful, your business model must be focused sharply on your customer. And it argues that you must think strategically about how to use your business model if you want to gain an advantage over your competitors.
Why business models matter -- Three business model lenses -- How the Bomgar box delivers customer value -- A ham radio company builds a superior business model -- TOMS shoes: selling a vision -- Netflix cancels the value exchange agreement -- Rent the runway: changing customer behaviors and industry norms -- J.C. Penney's big experiment -- Ten key ideas about business models -- Appendix A. Pricing mechanisms -- Appendix B. Online marketplaces -- Notes -- References -- Index.
Includes index.
Part of: 2013 digital library.
Mode of access: World Wide Web.
Keywords: Business planning